Building communities of practice: Pre-service teachers as content architects. (1st September 2017) - Shields, Sara Scott; Jesup, Cindy
In this visual essay we map a pedagogical exploration from conception to realization. Informed by scholarship in collaborative learning and inspired by the work of contemporary artist, Annalise Rees, we asked pre-service educators to visualize their instructional strengths and weaknesses through the construction of buildings. We asked our students to act as educational content architects, tasked with building a structure physically and conceptually reliant on collaboration and connection. This visual essay first explores collaborative learning in pre-service education through the lens of communities of practice. Next, the essay introduces the parameters of the assignment, before closing with an overview of student outcomes.